History as they lived it : a social history of Prairie du Rocher, Illinois - Brown, Margaret Kimball (Shawnee books., 2014)
"History as They Lived It deserves to be placed within the rich context of Illinois Country historiography going back more than a century. ... It brings together the fully ripened thoughts of a mature scholar at the very moment that students of the Illinois Country need such a book."--The foreword by Carl J. Ekberg Settled in 1722, Prairie du Rocher was at the geographic center of a French colony in the Mississippi Valley, which also included other villages in what is now Illinois and Missouri: Cahokia, Kaskaskia, Fort de Chartres, St. Philippe, Ste. Genevieve, and St. Lou